Brief report: Typical auditory-motor and enhanced visual-motor temporal synchronization in adults with autism spectrum disorder - Edey, R; Brewer, R; Bird, G; Press, C (Springer US, 2018)
The perception of subsecond durations in adults with autism spectrum disorder (hereafter ‘autism’; n = 25 Experiment 1, n = 21 Experiment 2) and matched typical adults (n = 24 Experiment 1, n = 22 Experiment 2) was examined by requiring participants to perform an action in time with auditory (Experiment 1) or visual (Experiment 2) events. Individuals with autism performed comparably to typical participants in the auditory task and exhibited less temporal error relative to their typical counterparts in the visual task. These findings suggest that perception of subsecond intervals is intact in autism, if not enhanced. Results support recent Bayesian theories of enhanced visual-perceptual precision in people with autism, and extend empirical support into the precision of subsecond temporal estimates.